Archetypal Social Systems Analysis: On the Deeper Structure of Human Systems - Mitroff, Ian I. (Academy of Management Review, 1983)
This paper extends the concept and method of stakeholder analysis, showing that the deeper symbolic aspects of human systems can be understood in terms of a special set of stakeholder entities known as archetypes. Archetypes are the most basic symbolic images that the human mind is capable of having and of experiencing. Archetypes and their associated properties are radically different from the kinds of stakeholders that are discussed in the typical analyses of social systems.